NON-FORMAL EDUCATION AS A TOOL OF INCREASING LEADER POTENTIAL OF STUDENTS IN PROFESSIONALLY TECHNICAL EDUCATIONAL INSTITUTIONS - Zhuravel, Tetyana; Rogozna, Yuliya (Educological discourse, 2018)
In the article the presented results of of theoretical research of the interpretation of informal education by domestic and foreign scholars; the essence of the concepts of "non-formal education", "formal education" and "informal education" ", "leader potential"; experience of introduction of the programs of informal education is analysed for teenagers and young people; the key results of research of features of leader potential of students of vocational educational establishments of the Donetsk area are reflected; base description is given to the platform of informal formation of "Studiyi Rozvytku " as instrument of increase of leader potential of students of vocational educational establishments; the further prospects of scientific searches are certain.